2017
DOI: 10.1080/09540121.2017.1382678
|View full text |Cite
|
Sign up to set email alerts
|

Perceived risks and benefits of quitting smoking in a sample of adults living with HIV/AIDS

Abstract: Persons living with HIV/AIDS (PLWH) smoke at high prevalences and experience significant smoking-related consequences. In community samples, perceived risks and benefits of quitting smoking are related to quit motivation and outcomes and are more strongly endorsed by women. This study examined perceived risks and benefits of quitting smoking and the relationship between risks and benefits and quit motivation and confidence in male and female PLWH. One hundred seven PLWH who reported current cigarette smoking c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…Individual barriers cited, including nicotine dependence, perceived risk of withdrawal, craving, and smoking for stress management, have been previously reported in the literature (Weinberger, Seng, Esan, & Shuter, 2017). These barriers prevented smokers from achieving abstinence despite knowing that smoking affected their health.…”
Section: Discussionmentioning
confidence: 89%
“…Individual barriers cited, including nicotine dependence, perceived risk of withdrawal, craving, and smoking for stress management, have been previously reported in the literature (Weinberger, Seng, Esan, & Shuter, 2017). These barriers prevented smokers from achieving abstinence despite knowing that smoking affected their health.…”
Section: Discussionmentioning
confidence: 89%
“…On the other hand, the results of Richmond [19] scale showed that a relatively important proportion present a moderate or high motivation to stop smoking, and this fact could be considered as favorable to intervention. To date, there are numerous studies that have examined attitudes of indi viduals and available interventions to quit smoking [10]. However, obstacles that hinder the implementation of these antismoking strategies exist; it was found that an individu al is more likely to stop smoking if he/she is provided with an appropriate information and tools [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…To date, there are numerous studies that have examined attitudes of indi viduals and available interventions to quit smoking [10]. However, obstacles that hinder the implementation of these antismoking strategies exist; it was found that an individu al is more likely to stop smoking if he/she is provided with an appropriate information and tools [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both major depressive disorder (MDD) and bipolar disorder (BD) are highly recurrent disorders that are characterized by increased risk for suicidal behaviours [1-3], lowered healthrelated quality of life (HR-QoL), increased disabilities [4][5][6][7], lowered socio-economic status [8][9][10][11], smoking behaviours [12][13][14], increased incidence of metabolic syndrome [15] and cognitive impairments including semantic memory deficits [16].…”
mentioning
confidence: 99%